Effect of carabeef substitution on the physical, chemical and sensory properties of beef/pork patties - Sua, Kirsten Ocampo
ABSTRACT Hamburger patties which are originally made from beef, are one of the popular processed meat products in the country and the demand for such products are expected to increase. However because of the shortage of local beef supply and its relatively high price, alternatives for beef are being explored. Buffalo meat or carabeef is widely used for meat manufacture in the country and is considered as an alternative for beef. The objective of this study is to determine the effect of buffalo meat on the physical, chemical and sensory properties of beef/pork patties. Beef/pork hamburger patties with 0, 30, 60 and 100 % carabeef substitution were cooked and refrigerated for zero, two and five days then frozen. Crude fat content was determined for both cooked and raw patties. Results for cooked patties were not significantly different across all formulations. The percent cooking loss decreased as the amount of carabeef increased. Peroxide values were higher for samples stored for five days compared to those stored for two days. Sensory analysis using fifty untrained panelists for over all acceptance and intensities of beef flavor, beef odor, juiciness, off flavor and off odor revealed significant differences in some attributes across all formulations. The substitution of beef with carabeef resulted in slight decrease in beef odor and flavor intensity and over all acceptability. The beef flavor and odor intensities might have been affected by off flavors and odors formed due to lipid oxidation and the differences in the composition of meats. The formation of warmed over flavor and aroma in cooked, refrigerated patties may be retarded by adding natural or synthetic antioxidants. Vacuum packaging and freezing may also help delay the process of lipid oxidation of such meat products and prolong their shelf life.